Spatial scenarios of potential electric vehicle adopters in Ireland - Arya Pillai; John A. Curtis; Miguel Angel Tovar Rea\~nos (The Economic and Social Research Institute (ESRI), 2021)
Transition to electric vehicles is among one public policy to reduce carbon emissions from the transport sector in Ireland. While EV adoption rates are increasing there is broad scepticism about achieving ambitious national policy targets. Using microdata on commuting behaviour and standardised assumptions based on existing literature, we identify candidates that could comfortably satisfy weekly driving needs using an EV without the need to alter behaviour for EV charging purposes. High density areas of potential candidates for transition to EVs are identified, particularly in specific urban areas of Cork and Dublin cities. We also find between 2 to 37% reduction in emissions from car owners based on the different set of assumptions we employ. While the per unit emission reduction in rural areas is higher, the aggregate emission reduction that can be achieved is higher in urban areas because of the higher density of candidates for transition in such areas. The charging infrastructure in these urban areas is already well-developed and marketing campaigns target ing groups such as environmentally conscious younger individuals, who are not often characterised as 'early adopters' in the literature, may pay off in such areas. Public campaigns with a local character in the areas with clusters of the candidates can be more effective in improving the adoption rates.
Keywords: 330; Elektrofahrzeug; Innovationsakzeptanz; Pendelverkehr; Konsumentenverhalten; Mikrodaten; Irland